Theory of change: community engagement as an intervention to create disaster resilience - Sutley, Elaina J.; Lyles, L. Ward (Frontiers in Built Environment, 2023)
Community resilience is a compelling problem that brings together many disciplines of study. Too often researchers wait until the end of research projects to disseminate findings, and may not include any intentional efforts toward technology translation. Convergence, and particularly the technology transfer aspects of convergence, should be a central goal for resilience research. This paper presents a theory of change proposing community engagement as the intervention needed for realizing actual community resilience. Three illustrative examples simultaneously demonstrate the need for the intervention and are used to provide guidance to researchers interested in learning how to engage. The first example illustrates investigator-driven research via post-hurricane reconnaissance coupled with experimental testing in a wind laboratory. The first example exemplifies technology transfer through regulatory changes. The second example illustrates community-based research via a post-tornado reconnaissance study, and exemplifies technology transfer through industry and outreach publications and public media. The third example illustrates community-driven research that developed a local climate plan, and incorporated the co-production of knowledge. The research translated throughout the project due to the community engaged approach leading to immediate adoption of the final research outcomes. Findings from this paper can be used to help other researchers determine the level of community involvement and navigate technology transfer options based on the goals and context of their own research.